PENGARUH SELF ASSESMENT SYSTEM, PENGETAHUAN, SANKSI, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WP. - Vania Vashtiany Sofyan; Tony Sudirgo (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine how the effect of self-assessment system, knowledge of taxation, tax sanctions, and tax socialization on individual taxpayer compliance in annual tax reporting. The sample was selected by purposive sampling method and the valid data were 100 taxpayers. The data processing technique uses multiple regression analysis assisted by the SPSS (Statistical Product and Service Solution) for Windows which was released 24 and Microsoft Excel 2013. The results of this study indicate that the self-assessment system has a significant effect on taxpayer compliance. Knowledge of taxation, tax sanctions, and socialization of taxation have no effect on taxpayer compliance. The implication of this research is the need for efforts, support, motivation from the government, especially the Directorate General of Taxes to convince taxpayers to participate in carrying out their tax obligations so that they have a good impact on the country.